A test of community assembly rules using foliar endophytes from a tropical forest canopy. (4th February 2020) - Donald, Julian; Roy, Mélanie; Suescun, Uxue; Iribar, Amaia; Manzi, Sophie; Péllissier, Léonie; Gaucher, Philippe; Chave, Jérôme
Abstract: Community assembly theory assumes that ecological communities are spatially delimited into patches. Within these patches, coexistence results from environmental filtering, competition and immigration. Truly delineated communities exist in laboratory studies of microbial cultures in Petri dishes, yet empirical tests conducted in continuous environments often use patches defined by convention as opposed to realized boundaries. Here we perform a test of ecological community assembly rules using foliar endophyte communities from a tropical rainforest, where leaves are considered as patches for both fungal and bacterial communities. We determined the diversity of fungal and bacterial endophytes using environmental DNA sequencing of 365 top‐canopy leaves, collected from 38 host trees belonging to 22 different species across a 4‐ha research plot. Three leaves were collected from three or more branches within each tree crown. We tested the effect of host tree species and their level of phylogenetic relatedness on community composition as well as the contribution of geographic distance between leaves to endophyte community diversity. Endophyte diversity significantly differed across host tree species, as did community composition. Within certain endophytic orders (Xylariales, Rhizobiales) species assemblages significantly differed across host tree species, but this trend was weaker or non‐existent in other orders known to contain pathogens and saprotrophs (Polyporales, Solirubrobacterales). Phylogenetically related host tree species displayed more similar endophyte communities than expected by chance, but geographically close trees did not. Consistent with the finding of host‐specificity, nearby leaves tended to host more similar communities than distantly positioned ones. These findings demonstrate that foliar endophytes are structured by dispersal across small spatial scales, but at the scale of the canopy they display patterns of neutral filtering, with only a small part of variation described by host tree differences. Endophyte communities thus act as a model system in evoking the rules predicted by theoretical community ecology. Abstract : Upper canopy leaves were sampled to determine endophyte community composition in a hyper diverse tropical rainforest. Fungal and bacterial community composition was determined by host branch, tree and species. Although phylogenetic and geographic distance explained variation at certain scales, neutral filtering best described patterns at the 4‐ha canopy plot scale. Translated Abstract: French Abstract La théorie d'assemblage des communautés suppose que les communautés écologiques soient spatialement délimitées. Au sein de chaque communauté, la coexistence d'espèces résulte de la sélection par des filtres environnementaux, la compétition et l'immigration. Délimiter des communautés est certainement possible au laboratoire, en boite de Pétri, mais reste parfois artificiel en dehors, et les communautés sont souvent définies par convention dans un habitat continu. Dans cet article, nous avons cherché à tester les règles d'assemblages en écologie des communautés sur un habitat délimité, que sont les feuilles et leurs communautés de champignons et bactéries endophytes. Nous avons évalué la diversité de ces deux groupes de micro‐organismes en séquençant l'ADN environnemental à haut débit sur 365 feuilles de canopée, récoltées sur 38 arbres hôtes et 22 espèces d'arbres situés sur 4 ha de forêt tropicale, au cœur de la Guyane française. Sur chaque arbre, plusieurs feuilles par branche et par individus ont été récoltées. Nous avons testé l'effet de l'hôte sur les communautés, et leur proximité phylogénétique, ainsi que l'effet de la distance géographique entre feuilles et individus d'arbre. La richesse et la composition des communautés d'endophytes était variable selon les hôtes, mais ce facteur reste peu explicatif. La distribution de certains ordres d'endophytes (Xylariales, Rhizobiales) était distincte selon l'espèce d'arbre, contrastant avec celle d'ordre contenant des potentiels pathogènes (Polyporales, Solirubrobacteriales). Tandis que des espèces d'arbres phylogénétiquement proches s'associaient à des communautés d'endophytes plus similaires qu'attendu au hasard, les communautés d'espèces voisines spatialement n'étaient pas particulièrement semblables. Enfin, au sein d'un individu, les communautés de feuilles voisines spatialement étaient aussi plus similaires que celle de feuilles distantes. Ces résultats soulignent qu'à faible distance, les communautés d'endophytes semblent structurées par la distance, et qu'à l'échelle de la canopée, les différences entres espèces n'expliquent qu'une petite partie des variations des communautés d'endophytes. Ce modèle semble effectivement utile pour tester la théorie d'assemblage des communautés. Notre étude souligne l'extrême diversité des endophytes tropicaux et montre le faible effet de l'hôte dans la structuration de ces communautés dans la canopée.